Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Novel hybrid nocodazole analogues as tubulin polymerization inhibitors and their antiproliferative activity - Kale, Sangram S.; Jedhe, Ganesh S.; Meshram, Sachin N.; Santra, Manas K.; Hamel, Ernest; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2015)
We describe the design, synthesis and SAR profiling of a series of novel combretastatin-nocodazole conjugates as potential anticancer agents. The thiophene ring in the nocodazole moiety was replaced by a substituted phenyl ring from the combretastatin moiety to design novel hybrid analogues. The hydroxyl group at the ortho position in compounds 2, 3 and 4 was used as the conformationally locking tool by anticipated six-membered hydrogen bonding. The bioactivity profiles of all compounds as tubulin polymerization inhibitors and as antiproliferative agents against the A-549 human lung cancer cell line were investigated Compounds 1 and 4 showed mu M IC50 values in both assays. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Anticancer; Colchicine; Nocodazole; Tubulin binding